2023
DOI: 10.1039/d2ob02191a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, kinetics and cellular studies of new phenothiazine analogs as potent human-TLK inhibitors

Abstract: The alterations in the expression patterns of protein kinases often implicate human cancer initiation and progression. Human Tousled-like kinases (TLKs), both TLK1/1B and TLK2 are evolutionary kinases found in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The published TLK2 inhibitors to date only offer compounds with moderate potency and poor kinome selectivity. 18,[62][63] In the present study, we demonstrate optimization of a chemotype for increased potency and selectivity for the clinically important TLK2 kinase. Since we achieved selectivity over the closest human paralog, TLK1, this work also provides important tool compounds for better characterization of the specific cellular functions of TLK2.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The published TLK2 inhibitors to date only offer compounds with moderate potency and poor kinome selectivity. 18,[62][63] In the present study, we demonstrate optimization of a chemotype for increased potency and selectivity for the clinically important TLK2 kinase. Since we achieved selectivity over the closest human paralog, TLK1, this work also provides important tool compounds for better characterization of the specific cellular functions of TLK2.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, we prepared a series of substituted oxindole amides, furnished with a standard HATU coupling, 49 in the presence of DIPEA and THF. The first set (60)(61)(62)(63)(64) was afforded in good yields (63-78 %), followed by a series of condensations under standard conditions to render a series of 5postion substituted amide final products (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76) in a range of yields (15-71%). The second set of amide substitutions (77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88) were also afforded in good to excellent yields (48-91%) followed by standard Knoevenagel conditions with the appropriate aldehyde to produce the condensation products (89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)…”
Section: Resultsmentioning
confidence: 99%
“…There are ongoing efforts to develop TLK1 and TLK2 inhibitors for targeting cancer cells with their promising roles in maintaining genome stability (64)(65)(66). Emerging evidence demonstrated that TLK1 and TLK2 are involved in cancer progression and therapeutic resistance (67)(68)(69)(70) and it has been shown that inhibition of TLK potentiates cell-killing in different types of cancers (1,(70)(71)(72)(73)(74), making TLK 1 and 2 attractive targets for therapeutic strategy development.…”
Section: Discussionmentioning
confidence: 99%
“…J54 also had favorable PKs, where plasma concentrations of 100ng/ml were reached 2h after IP injection (5 mg/kg), and ~6ng/ml was still detected after 24h [112] (better than THD [118]). While some of our newer compounds are more potent (some in the low nM) and more soluble than J54 [113], we are behind (compared to J54) on their specificity characterization and their in vivo PK/PD and tumor regression potency. Moreover, while the additional targets and possible sideeffects of PTHs are generally known (e.g., DR2 and hERG channel), the compounds with indole scaffold modification have less medical literature and records of FDA approval.…”
Section: Phenothiazines (Pth) As Tlk1 Inhibitorsmentioning
confidence: 99%
“…By employing in vitro kinase assays and conducting docking studies, we identified a novel PTH derivative, J54, with selective TLK inhibition and seemingly devoid of toxicity. Through our collaboration with a medicinal chemist and structural modelers, we have synthesized, modeled, and tested several custom-made PTH inhibitors of TLK1 [112,113]. Though the cellular target for the PTH-antipsychotics for cancer treatment remains unknown, studies have suggested their effects by inhibiting dopamine receptors [114,115].…”
Section: Phenothiazines (Pth) As Tlk1 Inhibitorsmentioning
confidence: 99%